Successful Treatment with Antibiotics Alone for Infant Rib Osteomyelitis - Yasuaki Matsumoto; Katsuyoshi Shimozawa; Junko Yamanaka; Yukari Atsumi; Tomomi Ota; Shinji Mochizuki; Hiroyuki Shichino (Hindawi Limited, 2022)
Pediatric rib osteomyelitis is a rare disease occurring predominantly in the neonatal period and early childhood and accounting for about 1% of all pediatric osteomyelitis. Compared to osteomyelitis in other parts of the body, pediatric rib osteomyelitis shows few localized findings (such as redness and swelling) and often an indolent lesion as well either of which may delay diagnosis and thus make treatment more difficult. A previously healthy one-year-old girl came to our department with a chief complaint of fever lasting for three days. She was admitted to our department to investigate her fever. At the time of admission, radiographs showed decreased permeability in the left lung field; so, we started antimicrobial therapy on the assumption of pneumonia. On the second day of admission, methicillin-susceptible Staphylococcus aureus was detected in the blood culture. A further, more detailed physical examination revealed some slight left anterior chest swelling. We performed a contrast-enhanced CT scan and an MRI and diagnosed her with rib osteomyelitis complicated with a chest wall abscess. She was given intravenous cefazolin for two weeks, switched to oral cephalexin for four weeks, and then recovered completely. She was treated without surgical intervention, having showed a good response to antimicrobial therapy. Osteomyelitis of the ribs in children is reported to be more common in the lower ribs and to occur more frequently in infants. In many cases, the earliest symptoms are nonspecific, so careful examination to detect any subtle abnormalities-such as swelling or mass-is of key importance for early diagnosis in infants. Regarding treatment, most cases of hematogenous osteomyelitis resolve with antimicrobial therapy alone-although surgical intervention may be required in cases of poor response to antimicrobial therapy. Therefore, early diagnosis of rib osteomyelitis through careful physical examination may reduce the chances of requiring surgical intervention.